A hexagon in Saturn’s northern stratosphere surrounding the emerging summertime polar vortex - Fletcher, L; Orton, G; Sinclair, J; Guerlet, S; Read, P; Antunano, A; Achterberg, R; Flasar, F; Irwin, P; Bjoraker, G; Hurley, J; Hesman, B; et al. (Springer Nature, 2018)
Saturn’s polar stratosphere exhibits the seasonal growth and dissipation of broad, warm vortices poleward of ~75° latitude, which are strongest in the summer and absent in winter. The longevity of the exploration of the Saturn system by Cassini allows the use of infrared spectroscopy to trace the formation of the North Polar Stratospheric Vortex (NPSV), a region of enhanced temperatures and elevated hydrocarbon abundances at millibar pressures. We constrain the timescales of stratospheric vortex formation and dissipation in both hemispheres. Although the NPSV formed during late northern spring, by the end of Cassini’s reconnaissance (shortly after northern summer solstice), it still did not display the contrasts in temperature and composition that were evident at the south pole during southern summer. The newly formed NPSV was bounded by a strengthening stratospheric thermal gradient near 78°N. The emergent boundary was hexagonal, suggesting that the Rossby wave responsible for Saturn’s long-lived polar hexagon—which was previously expected to be trapped in the troposphere—can influence the stratospheric temperatures some 300 km above Saturn’s clouds.